Wind Induced Response of Spar-mooring-riser System - Eyada Ibrahim, Abdulrahman; Jameel, Mohammed (Springer Verlag (Germany), 2018)
In recent decades, the exploitation of hydrocarbon reservoirs under the seas and oceans has been regarded as a viable alternative. Several types of floating structures are utilized in deep and ultra-deep water oil and gas exploration and production. Spar platforms are the most recent type of platforms to be designed and utilized in deep water environments. This type of platform is an assemblage of a cylindrical hull, moorings and risers that responds to hydrodynamic and aerodynamic loads in a complex manner. Coupled behaviours of spar–mooring–riser system influenced by the wind load in random wave environment have been studied using coupled analysis method. The spar–mooring–riser system has been analysed to predict system responses induced by wind action under a long crested random wave using finite element approach. Wind load induces a significant shift in the spar position away from its original place in the random sea state in addition to a notable heave motion reduction. The top tension magnitude of the moorings and riser significantly increased. The diminishing fluctuation highlights the firmness and controlled oscillations of the spar platform relative to its new mean position.